Propagating material instabilities in planar architectured materials. (1st October 2020) - Viard, Antoine-Emmanuel; Dirrenberger, Justin; Forest, Samuel
Graphical abstract: Abstract: Under tension low carbon steel exhibits inhomogeneous plastic deformation. This instability called Piobert-Lüders banding creates fronts of localized strain that propagate in the structure. To date, Lüders banding has been studied experimentally and numerically only in simple geometries like sheets, tubes and normalized fracture mechanics specimens. This paper focuses on architectured materials and specifically lattice structures which can be defined as a tessellation of unit-cells periodically distributed in space. This class of advanced materials draws new mechanical properties from its inner architecture. We investigate the effect of the architecture on the global behavior of the structure. Especially, how bands interact with the lattice and how to control initiation and propagation of localized strain using the architecture. An elastoplastic material model is used in order to simulate the Piobert-Lüders band formation and propagation. The model also considers a large deformation framework for elastoplasticity with periodic boundary conditions in order to represent the architectured material. Initiation and propagation of material instabilities depend on the geometry as well as its on the relative orientation with respect to the loading direction. Propagating and non-propagating behaviors are identified for the Piobert-Lüders bands and related to the different types of geometry. Material instabilities affect the mechanical behavior of the structure as far as they are governed by the architecture. These conclusions are compared to experimental results from tensile tests on laser-architectured specimens made of ARMCO steel.